RISK MITIGATION IN SAUSAGE PRODUCTION USING A COMBINATION OF SUPPLY CHAIN OPERATIONS REFERENCE (SCOR) AND HOUSE OF RISK (HOR) METHODS - Bastian Trimaryono; Wiwik Sulistiyowati (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to identify risk factors that affect product quality in the sausage production process at PT Ciomas Adisatwa and determine appropriate mitigation measures to address these risks. Method: The methods used are SCOR mapping and House of Risk (HOR). In HOR phase 1, risk events and risk agents were identified, severity and occurrence were assessed, correlations between risk events and risk agents were determined, and ARP values were calculated. Result: The results identified 17 risk events and 24 risk agents, with the highest ARP values in A3, A6, and A10. In the second phase of the HOR, seven mitigation strategies were developed. Some of the highest-priority strategies included PA2, PA5, and PA6. Novelty: The novelty of the study lies in the combination of SCOR mapping and House of Risk to identify and mitigate risks in the production flow, offering a structured approach to improve product quality in the sausage production process.